PENGARUH TINGKAT PENDIDIKAN, PENGELUARAN PEMERINTAH DAN UPAH MINIMUM REGIONAL TERHADAP TINGKAT PENGANGGURAN DI JAWA BARAT TAHUN 2017-2021 - Mahardika, Kukuh Dwi; Nurul Badriyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study examines of the education level, government spending, and regional minimum wages on the unemployment rate in West Java in 2017–2021. This study uses a quantitative method with a type of data that is Panel Data. Panel data is a combination of cross-sectional data covering 27 regencies and cities in West Java Province and a time series for five years from 2017 to 2021. Model analysis uses panel data regression, and the results found that the best approach model is the Fixed Effect ModeI approach (FEM) using the Eviews 12 platform. Data collection was carried out by documenting data at the West Java Central Statistics Agency (BPS), West Java OpenData, and other government-owned official data portals. Based on the results of the simultaneous tests that have been carried out, variable employment, education level, government spending, and regional minimum wages have an influence on the unemployment rate.